1992
DOI: 10.1002/ajmg.1320420124
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypically dissimilar hypophosphatasia in two sibships

Abstract: Autosomal dominant and autosomal recessive forms of hypophosphatasia have been reported; generally the clinical picture runs true to form in families. In each of 2 kindreds, 2 sibs were clinically affected by hypophosphatasia to a markedly different extent. One set of sibs showed the lethal (perinatal) and infantile forms. The other showed the dental and adult forms. In both families there was consanguinity, albeit distant, and clinical expression in sibs supporting autosomal recessive inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Therefore, patients with different clinical types existed in the same family in this case. Similar cases have been described in the same family with childhood-type and adult-type disease [3,24].…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, patients with different clinical types existed in the same family in this case. Similar cases have been described in the same family with childhood-type and adult-type disease [3,24].…”
Section: Discussionsupporting
confidence: 78%
“…Two siblings of HPP in our case showed considerable discordant severity in the fetal period. Although genotype-phenotype correlations have been widely described with regard to HPP (Zurutuza et al, 1999), several reports have demonstrated the discordance in calcification and fetal growth in HPP siblings with the same ALPL gene mutation (Macfarlane, Kroon, & van der Harten, 1992). Stevenson et al (2008) showed discordant phenotype of HPP siblings, although both had compound heterozygous mutation in ALPL gene (c.526G>A and c.814C>T).…”
Section: Discussionmentioning
confidence: 96%
“…Although genotype-phenotype correlations have been widely described with regard to HPP (Zurutuza et al, 1999), several reports have demonstrated the discordance in calcification and fetal growth in HPP siblings with the same ALPL gene mutation (Macfarlane, Kroon, & van der Harten, 1992). Although genotype-phenotype correlations have been widely described with regard to HPP (Zurutuza et al, 1999), several reports have demonstrated the discordance in calcification and fetal growth in HPP siblings with the same ALPL gene mutation (Macfarlane, Kroon, & van der Harten, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Seizures have also been reported in severe cases (Heitzman and Ferguson, 1967;. Hypophosphatasia is usually inherited as an autosomal recessive trait, although it can display variable expressivity and incomplete penetrance (Whyte et al, 1982;MacFarlane et al, 1992). Autosomal dominant inheritance of the adult form of hypophosphatasia has also been observed (Whyte et al, 1979).…”
Section: Introductionmentioning
confidence: 99%